“Emotion is Another Kind of Information”: (Re)imagining Care Through Art Explorations - Hellstrand, Ingvil; Koistinen, Aino-Kaisa; Simonhjell, Nora; Søraa, Roger Andre; Tapio, Hege (Art/Research International)

(untitled) (University of Alberta, 2024)
This review explores entanglements of the theoretical and affective impacts of an art exhibition called Caring Futures which was part of an interdisciplinary research project. The review is a qualitative analysis of the exhibition, and is interspersed with our experiential, affective, and creative reflections and responses to the exhibition. Creative and imaginative approaches inspire us as researchers and supported our interactions with this exhibition in ways that opened new spaces for knowledge production. Our experiences highlight the value of arts-based methodologies for exploring questions of vulnerability and care. Foregrounding subjective and affective responses is risky in scientific work and confronts conventional boundaries for academic knowledge production. Honoring meetings between art and research(ers) can productively challenge taken-for-granted norms involved in undertaking academic research.